Indonesian Folklore Movie as a Media to Teach Listening: An Experimental Study - Khusnul Khuluqin Nisak (SMA Negeri 1 Bangkinang Kota, 2025)
This study aims to test the effectiveness of Indonesian folklore films as a medium in teaching English listening comprehension to vocational school students. Using a quantitative approach with an experimental design, this study uses a pretest-post-test control group design to assess the improvement of students' listening skills. A total of 30 students were divided into two groups: an experimental group taught using Indonesian folklore films and a control group taught through conventional audio material. Data collected using standard listening tests before and after the intervention. Test scores were analyzed using SPSS version 25. Paired sample t-tests were performed to test the significance of the difference between pretest and posttest scores. The results showed a significant improvement in the posttest score of the experimental group (Mean = 84.13) compared to the pretest score (Mean = 78.00), with a significance value of 0.000 (p < 0.05), which showed a significant influence. These findings suggest that Indonesian folklore films can improve students' listening comprehension by offering a familiar and culturally interesting audiovisual context. The visual and emotional elements in folklore narrative help students understand spoken English better, making the learning process more effective and enjoyable.